ASPECTS REGARDING THE PRODUCTION AND MARKETING OF CEREALS IN THE BLACK SEA BASIN AREA - Irina-Adriana CHIURCIU; Elena SOARE; Dan Marius VOICILAȘ; Ion CERTAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Cereals are the most produced commodity worldwide, according to statistical data. Among the top ten countries in the list of the most important producers of corn and wheat respectively, as well as among the largest exporters of these categories of cereals, there are two countries located in the Black Sea basin, Ukraine and the Russian Federation. Other important competitors in the region were Romania and Turkey, who took 3rd or 4th place in corn or wheat production. At the same time, Romania occupied the 6th place in the ranking of corn exporters worldwide and 9th in that of wheat exporters in 2021. In addition to the four states mentioned before, in the paper, in the area related to the maritime basin, Armenia, Bulgaria, Georgia, Azerbaijan, Republic of Moldova and Greece were also included. The paper aimed to provide a coherent picture of competitiveness on the grain market, at the Black Sea basin level, and, at the same time, to highlight the position that Romania occupies in the economy of the area and in the world grain trade. For this purpose, the areas cultivated with corn and wheat were presented, as well as the productions obtained in the period 2015-2021 in the countries of the area related to the Black Sea basin, then the value imports and exports of corn and wheat that these countries recorded.